A comparison of the intrasubject variation in drug exposure between generic and brand‐name drugs: a retrospective analysis of replicate design trials. (15th January 2016) - Yu, Yang; Teerenstra, Steven; Neef, Cees; Burger, David; Maliepaard, Marc
Abstract : AIMS: The aim of the present study was to investigate whether differences in total and peak drug exposure upon generic substitution are due to differences between formulations or to intrasubject pharmacokinetic variability of the active substance. Methods: The study was designed as a retrospective reanalysis of existing studies. Nine replicate design bioequivalence studies representing six drug classes – i.e. for alendronate, atorvastatin, cyclosporin, ebastine, exemestane, mycophenolate mofetil, and ropinirole – were retrieved from the Dutch Medicines Regulatory Authority. Results: In most studies, the intrasubject variability in total and peak drug exposure was comparable for the brand‐name [in the range 0.01–0.24 for area under the concentration–time curve (AUCt ) and 0.02–0.29 for peak plasma concentration (Cmax ) on a log scale] and generic (0.01–0.23 for AUCt and 0.08–0.33 for Cmax ) drugs, and was comparable with the intrasubject variability upon switching between those drugs (0.01–0.23 for AUCt and 0.06–0.33 for Cmax ). The variance related to subject‐by‐formulation interaction could be considered negligible (–0.069 to 0.047 for AUCt and –0.091 to 0.02 for Cmax ). Conclusion: In the investigated studies, the variation in total and peak exposure seen when a patient is switched from a brand‐name to a generic drug is comparable with that seen following repeated administration of the brand‐name drug in the patient. Only the intrasubject variability seems to play a crucial and decisive role in the variation in drug exposure seen; no additional formulation‐dependent variation in exposure is observed upon switching. Thus, our data support that, for the medicines that were included in the present investigation, from a clinical pharmacological perspective, the benefit–risk balance of a generic drug is comparable with that of the brand‐name drug.